A 2D Cd(II)-MOF as a multifunctional luminescencent sensor for nitroaromatics, iron(III) and chromate ions. Issue 6 (19th March 2017) - Wu, Yu; Li, Yulong; Zou, Like; Feng, Jianshen; Wu, Xiren; Yang, Suzhen; Liu, Weicong; Fan, Guiling; Singh, Amita; Kumar, Abhinav
Abstract: A Cd(II)-MOF, [Cd(L)(4, 4′-bipy)]·H2 O·DMFn (1 ) (L = nicotinic acid (2, 4-dihydroxybenzylidene)-hydrazide and 4, 4′-bipy = 4, 4′-bipyridine), has been synthesized and characterized by microanalyses, FTIR, TGA, and single-crystal X-ray diffraction. Additionally, powder X-ray diffraction was performed to check the phase purity of the synthesized compound. Single-crystal X-ray diffraction reveals that1 has a 2D grid network. Photoluminescent sensing of nitrobenzene, Fe(III) and CrO4 2− ions indicates that1 could be a candidate for developing selective luminescent sensors for these species. Theoretical calculations have been performed to gain insight into the possible mechanism of quenching effect in emission on addition of nitrobenzene in1 which supports the mechanism operating through ground state charge transfer between1 and nitrobenzene. Abstract :